2018
DOI: 10.1186/s12933-017-0645-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of speckle-tracking echocardiography with invasive hemodynamics for the detection of characteristic cardiac dysfunction in type-1 and type-2 diabetic rat models

Abstract: BackgroundMeasurement of systolic and diastolic function in animal models is challenging by conventional non-invasive methods. Therefore, we aimed at comparing speckle-tracking echocardiography (STE)-derived parameters to the indices of left ventricular (LV) pressure–volume (PV) analysis to detect cardiac dysfunction in rat models of type-1 (T1DM) and type-2 (T2DM) diabetes mellitus.MethodsRat models of T1DM (induced by 60 mg/kg streptozotocin, n = 8) and T2DM (32-week-old Zucker Diabetic Fatty rats, n = 7) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 42 publications
3
26
0
2
Order By: Relevance
“…Our findings indicated that hemodynamic parameters such as systolic, diastolic, and mean blood pressures were altered in DC and DC + ISO rats due to the consecutive loss of cell membrane potential in injured myocardium. The results are in line with the previous reports (Ishikawa et al, ; Kalkan et al, ; Mátyás et al, ). Moreover, KF treatment improved systolic, diastolic, and mean blood pressures in DC + ISO rats.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings indicated that hemodynamic parameters such as systolic, diastolic, and mean blood pressures were altered in DC and DC + ISO rats due to the consecutive loss of cell membrane potential in injured myocardium. The results are in line with the previous reports (Ishikawa et al, ; Kalkan et al, ; Mátyás et al, ). Moreover, KF treatment improved systolic, diastolic, and mean blood pressures in DC + ISO rats.…”
Section: Discussionsupporting
confidence: 94%
“…Speckle-tracking echocardiography emerged as a valuable tool for a more quantitative, semi-automated approach. Global longitudinal strain is showing an established diagnostic and prognostic value regarding LV pathologies [ 8 ], and promising data also have been gathered for the RV [ 9 ]. Although the RV longitudinal strain has an established added prognostic value compared to TAPSE, longitudinal strain still incorporates only one motion direction.…”
Section: Advanced Echocardiographic Techniques To Characterize Rv Mecmentioning
confidence: 99%
“…However, the link between myocardial deformation and underlying changes in structural proteins in the context of diabetic cardiomyopathy is still little explored. Only a few studies 5,24,35 have determined global LV function via strain parameters in the context of experimental diabetic cardiomyopathy so far. Therefore, the aim of our study was to evaluate myocardial deformation in combination with the underlying changes in the expression of structural components during the pathogenesis of STZ-induced type 1 diabetes mellitus-associated diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%